Role of Availability on Actual Purchase Behavior of Organic Food Products: An Application of Theory of Planned Behavior - Painuly, Poonam; Pachaury, Prachi (Current Nutrition & Food Science, 2024)
Aim: This paper examines how consumers' purchase intentions and actual purchase behavior for organic food products are related to the moderating effect of availability and its relationship with those two variables. Methods: Using structural equation modeling, a structured survey of 250 participants revealed that the three components of the theory of planned behavior-attitude, subjective norm, and perceived behavior control impacted consumers' purchase intentions. Results: Findings revealed a strong correlation between purchase intention and actual purchase behavior of the consumers towards organic products. Furthermore, it identifies a few areas for future work that would benefit wholesalers, retailers, marketers, consumers, and scholars. Conclusion: Food provides indispensable nourishment, which leads to a healthy life. However, it has recently come to light that many food products have become unhealthy due to farmers' excessive use of pesticides and chemical-based fertilizers, resulting in several illnesses. Currently, it has been observed that many consumers are attracted to organic food that is healthy, tasty, and free from chemicals, pesticides, and fertilizers. To increase the study's accuracy and utility, further research might be done on additional aspects, such as significant price premiums, a lack of knowledge, confidence in organic certification programs, and quality.
Keywords: Organic food product